24. INVESTIGATION ON THE USE AND THERAPEUTIC VANCOMYCIN MONITORING AT NGUYEN TRAI HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To survey the characteristics of infection, characteristics of Vancomycin use, monitoring of Vancomycin blood concentration and treatment results at Nguyen Trai Hospital, Ho Chi Minh city.Methods: A descriptive cross-sectional study was conducted on 82 records with indication of Vancomycin  concentration monitoring at Nguyen Trai Hospital from June 1, 2023 to February 29, 2024.Results: 86.6% of the patients had renal impairment and 21.9% of the patients were on hemodialysis. Approximately 29.6% of all patients were identified as positive for Gram-positive bacteria, with 87.5% of these having MIC of Vancomycin ≤ 1 mg/L. In the non-dialysis group, the rates of achieving target AUC/MICs were 23.3% and 66.7% respectively for intermittent infusion and continuos infusion. In the dialysis group, 8.3% of patients on intermittent dialysis and 33.3% of those on continuous dialysis achieved the target ranges. Acute kidney injury was observed in 9.7% of patients, classified as R and I according to the RIFLE criteria with equal percentages of 4.9%.Conclusion: The proportion of patients achieving therapeutic targets was comparatively low. Nguyen Trai Hospital needs to implement specific protocols for special patient subpopulations, guidelines on calculating proper dosing regimens for renal impairement patients.
Keywords: Vancomycin; therapeutic drug monitoring, elderly patients.